2017
DOI: 10.1186/s12944-017-0487-5
|View full text |Cite
|
Sign up to set email alerts
|

Citrus lemon essential oil: chemical composition, antioxidant and antimicrobial activities with its preservative effect against Listeria monocytogenes inoculated in minced beef meat

Abstract: BackgroundLemon (Citrus limon) is a flowing plant belonging to the Rutaceae family. Citrus plants constitute one of the main valuable sources of essential oil used in foods and medicinal purposes.MethodsIn this study, we assessed chemical composition, antioxidant and antimicrobial activities of C. limon essential oil (ClEO) with its preservative effect against Listeria monocytogenes inoculated in minced beef meat. Gas chromatography/mass spectrometry (GC-MS) was used to identify the major components of the obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
148
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(164 citation statements)
references
References 41 publications
12
148
2
2
Order By: Relevance
“…A total of four terpene components were identified in the essential oil: α‐pinene, sabinene, myrcene, and limonene. These results confirm the presence of limonene as the principal component of the essential oils from different types of citrus peels …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…A total of four terpene components were identified in the essential oil: α‐pinene, sabinene, myrcene, and limonene. These results confirm the presence of limonene as the principal component of the essential oils from different types of citrus peels …”
Section: Resultssupporting
confidence: 81%
“…These results confirm the presence of limonene as the principal component of the essential oils from different types of citrus peels. [15][16][17] Gomes et al 14…”
Section: Yield and Chemical Composition Of Essential Oilmentioning
confidence: 99%
“…Citrus plants constitute one of the most valuable and important sources of essential oil served in food processing and medical use. Citrus limonum essential oil was reported to have antimicrobial activities with preservative effect against Listeria monocytogenes inoculated in minced beef meat [28], and remarkable miticidal activity in vitro and in vivo applications against sarcoptic mange in rabbits [29]. Besides, the essential oil from Citrus limetta Risso peels could alleviate skin inflammation, both tested in vitro and in vivo [30], while the essential oil from Citrus aurantium L. var.…”
Section: Discussionmentioning
confidence: 99%
“…Applying and expanding the latter in vitro findings, in 2017 a team in Tunisia reported that lemon EO added to minced beef meat successfully inhibits development of L. monocytogenes in meat treated with EO at a concentration between 0.06 and 0.312 mg of EO per g of meat ( Figure ), reducing the growth of the bacteria by 2.5 log cycles after 4 and 6 days of storage at 4 °C, respectively, thereby opening “new promising opportunities for the prevention of contamination from and growth of pathogenic bacteria… during minced beef meat storage at 4 °C.” [ 25 ]…”
Section: New Research On Lemonmentioning
confidence: 99%
“…Reproduced under the terms of the Creative Commons Attribution 4.0 International License. [ 25 ] Copyright 2017, The Authors.…”
Section: New Research On Lemonmentioning
confidence: 99%